Analisis Performa PLTSOff -Grid 1 kWp Di Selasar Gedung Laboratorium Politeknik Negeri Jakarta - Hidayati, Noor; Sitorus, Andre Halomoan; Widiyatmoko, Widiyatmoko; ekayuliana, Arifia (Fakultas Teknik UMSU, 2024)
The performance analysis of a 1 kWp off-grid Solar Power Plant (SPP) located on the terrace of the Energy Laboratory Building at Jakarta Polytechnic was conducted to determine the SPP's performance. The analysis involved comparing the design data with the actual installed system conditions. The methodology employed manual calculation of the SPP's power generation and simulation of its performance using PVSyst software. The analysis results indicated that the current performance ratio of the SPP is only 11%, primarily due to the low direct utilization of solar energy. A recommendation provided is to increase the load on the SPP system. Simulations conducted on the recommended load increase demonstrated a significant improvement in the performance ratio, with a value of 58%.